Occult Hepatitis B : A Hidden Threat (TAJ: Journal of Teachers Association, 2010)
Occult hepatitis B (OHB) is defined as the presence of HBV-DNA in liver with or without detectable HBV DNA in serum in patients who are HBsAg negative in currently available assays. Diagnosis of occult HBV infections requires sensitive HBV-DNA PCR assay. Though reports of occult hepatitis B infections are coming from almost every corner of the world, the exact prevalence of this hidden menace is still not know. Several aspects of occult hepatitis B infection are still not resolved including its clinical significance relating to the molecular basis, risk of transmission, reactivation and progression to chronic liver disease. In this review article, we will try to explore the current concepts and clinical implications of occult hepatitis B virus infection.TAJ 2010; 23(1): 109-113